Functional connectivity in the default network during resting state is preserved in a vegetative but not in a brain dead patient - Boly, M.; Tshibanda, L.; Vanhaudenhuyse, A.; Noirhomme, Q.; Schnakers, C.; Ledoux, D.; Boveroux, P.; Garweg, C.; Lambermont, B.; Phillips, C.; Luxen, A.; Moonen, G.; et al. (Human brain mapping, 2009)
Recent studies on spontaneous fluctuations in the functional MRI blood oxygen level‐dependent (BOLD) signal in awake healthy subjects showed the presence of coherent fluctuations among functionally defined neuroanatomical networks. However, the functional significance of these spontaneous BOLD fluctuations remains poorly understood. By means of 3 T functional MRI, we demonstrate absent cortico‐thalamic BOLD functional connectivity (i.e. between posterior cingulate/precuneal cortex and medial thalamus), but preserved cortico‐cortical connectivity within the default network in a case of vegetative state (VS) studied 2.5 years following cardio‐respiratory arrest, as documented by extensive behavioral and paraclinical assessments. In the VS patient, as in age‐matched controls, anticorrelations could also be observed between posterior cingulate/precuneus and a previously identified task‐positive cortical network. Both correlations and anticorrelations were significantly reduced in VS as compared to controls. A similar approach in a brain dead patient did not show any such long‐distance functional connectivity. We conclude that some slow coherent BOLD fluctuations previously identified in healthy awake human brain can be found in alive but unaware patients, and are thus unlikely to be uniquely due to ongoing modifications of conscious thoughts. Future studies are needed to give a full characterization of default network connectivity in the VS patients population. Hum Brain Mapp, 2009. © 2009 Wiley‐Liss, Inc.